Commissioning the Truth - Orford, Anne (Columbia Journal of Gender and Law, 2006)
This Article was originally written as an invited contribution to a workshop on Gender and Transitional Justice organized by the International Centre for Transitional Justice. My particular assignment for that workshop was to write a discussion paper which addressed the key category of “truth.” The idea of truth has a particularly potent role to play in the world of transitional justice. For many scholars and practitioners in this field, uncovering the truth is understood as a vital task, both at an individual and at a collective level. At the individual level, truth-telling is presented in therapeutic terms, as a means of healing those who have been wounded by the violence of civil war, revolution, or despotism. At the collective level, establishing the truth of a contested history is understood as a necessary basis for moving forward as a nation and creating the conditions for a viable, shared life. The title of this Article indicates a certain distance from this vision of the ends of truth. In particular, the word “commissioning” is there as a reminder. Throughout, this Article makes visible the institutional conditions and productive effects of the commissioning of truth. Testimony or speech becomes part of commissioned truth through institutional mediation-through the institutions of language, of the state, and of liberal internationalism. How should we try to understand what takes place when an international body, a state, or a private organization seeks to write the truth of history? How should we understand the situation of the subject who is called upon to speak her truth in such a context? What does the act of writing a commissioned truth bring into being? What does the commissioning of an official truth mean for the addressees of such performances?